Development of flipped classroom math learning instruments with advocacy-sociograph - Zainnur Wijayanto; Indah Ayu Rukmana; Betty Kusumaningrum; Elang Amadeus Poort (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The research project described aims to create a Math learning media with a flipped classroom model on "Polyhedron of Cube and Block" for grade VIII Junior High School students. This device uses the advocacy-sociograph approach. This research uses three stages of development, namely Defining, Designing, and Developing. After conducting data analysis, it can be concluded that the results of the validation of the lesson plan are valid, indicating that it is well-designed and suitable for teaching the targeted mathematics content. Similarly, the e-LKPD (e-worksheet) also received very valid validation results, indicating that the e-LKPD is very suitable and adequate to facilitate student learning. These positive validation results indicate that the learning tools in lesson plans and LKPDs (worksheets) based on the flipped classroom approach with advocacy-sociographs are valid and feasible for further testing. The researchers recommend this learning tool as a reliable reference source for mathematics learning in Junior High School.